Association between the Socioeconomic Factors, Healthy Home, and Healthy Behavior among Parents of Toddler with Acute Respiratory Infection in Kediri, Indonesia - Tiyan Anggraini; Ambar Mudigdo; RB. Soemanto (Masters Program in Public Health, 2016)
Background: Acute Respiratory Infection or ARI is the most deaths occurred in toddler. Many factors lead to a high incidence of this disease among socioeconomic, healthy home and healthy behavior of parents. This study was aimed to determine the association between socioeconomic and healthy homehealthy home with healthy behavior in parents of toddler with acute respiratory infections.Subject and Methods: This was a case study conducted in Kediri, East Java, Indonesia. A total of 100 toddlers consisted of 20 toddlers and parents with ARI and 80 toddlers with parents without ARI. The dependent variable was parents of toddlers with acute respiratory infection. The independent variables included socioeconomic and healthy home with healthy behavior. The data were collected by pre-tested questionnaire, and analyzed using a multiple logistic regression model.Results: Theresults obtained by the education (OR = 9.1; 95%CI = 0.8 to 98.4; p = 0.001), family income (OR = 1.3; 95% CI = 0.1 to 14.2; p = 0.000), housing components (OR = 4.0, 95%CI = 0.5 to 27.7; p = 0.005), sanitation (OR = 6.9; 95% CI = 1.1 to 41.9; p = 0.001), healthy behavior (OR = 8.9; 95% CI = 1.6 to 48.7 ; p = 0.003).Conclusion: The results of this study concluded that education, family income, housing components, sanitation and behavior of the occupants had a statistically significant relationship to healthy behaviors parents of toddlers with ARI.Keywords: education, family income, housing components, sanitation, healthy behavior, and healthy behavior parents of toddler patients with Acute Respiratory Infections (ARI).Correspondence: Tiyan Anggraini. School of Health Sciences, Kadiri University, Kediri, Indonesia. Email: tiyananggraini@yahoo.co.idJournal of Epidemiology and Public Health (2016), 1(1): 66-74https://doi.org/10.26911/jepublichealth.2016.01.01.08